Small-mammal abundance and species diversity: land use and seasonal influences in the Serengeti Ecosystem, Tanzania - Shilereyo, Monica T.; Magige, Flora J.; Ogutu, Joseph O.; Røskaft, Eivin (Frontiers in Conservation Science, 2023)
Land use, habitat suitability and seasonality can fundamentally shape small mammal abundance, species richness, diversity, evenness and composition. However, how these characteristics of small mammals are determined by land use, habitat type and rainfall seasonality is still poorly understood for most ecosystems. We analyse how land use (total protection in a national park, pastoralism and crop agriculture), habitat type and rainfall seasonality, influence small mammal relative abundance, species richness and diversity in the Tanzania Serengeti Ecosystem. We used 141 live traps to capture 612 small mammals in the wet and dry seasons of 2017 and 2018. Relative abundance was higher in the pastoral land than in the park or agricultural land; and in the dry season in all the three land use types. Species richness and diversity were the highest in the park, middling in the agricultural land and the lowest in the pastoral land. The high relative abundance in the pastoral land was due to the numerical dominance of two generalist species in the shrubland (grass rat Arvicanthis niloticus) and cropland (multimammate rat Mastomys natalensis), resulting in low species richness and diversity. High species richness and diversity in the park indicate high habitat heterogeneity whereas high species diversity in the agricultural land during the dry season reflects high food availability during and soon after harvests. Thus, human activities apparently exert deleterious effects on some small mammal species by reducing the suitability of their habitats, species richness and diversity and increasing risks of human-rodent conflicts.